Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.31
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Cross-Lingual Semantic Role Labeling with Heterogeneous Linguistic Resources

Abstract: While cross-lingual techniques are finding increasing success in a wide range of Natural Language Processing tasks, their application to Semantic Role Labeling (SRL) has been strongly limited by the fact that each language adopts its own linguistic formalism, from Prop-Bank for English to AnCora for Spanish and PDT-Vallex for Czech, inter alia. In this work, we address this issue and present a unified model to perform cross-lingual SRL over heterogeneous linguistic resources. Our model implicitly learns a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Furthermore, we also find that fine-tuning all parameters leads to slightly better performance than freezing the language model during the CSRL training stage. This finding is consistent with the previous work (Conia et al, 2021). For the pre-training objectives, we found that (1) removing TLM & HPSI objective hurts the performance consistently but slightly; (2) SPI & UOR objectives help the model to better identify the cross-arguments; (3) SAI objective helps to find intra-arguments on DuConv and Persona-Chat, but might hurt the F1 intra score on CMU-DoG; (4) hierarchical pre-training is superior to end-to-end pre-training which simultaneously optimizes all auxiliary objectives.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, we also find that fine-tuning all parameters leads to slightly better performance than freezing the language model during the CSRL training stage. This finding is consistent with the previous work (Conia et al, 2021). For the pre-training objectives, we found that (1) removing TLM & HPSI objective hurts the performance consistently but slightly; (2) SPI & UOR objectives help the model to better identify the cross-arguments; (3) SAI objective helps to find intra-arguments on DuConv and Persona-Chat, but might hurt the F1 intra score on CMU-DoG; (4) hierarchical pre-training is superior to end-to-end pre-training which simultaneously optimizes all auxiliary objectives.…”
Section: Resultssupporting
confidence: 94%
“…Cross-lingual Language Model (CLM) We concatenate all utterances into a sequence and then use a pre-trained cross-lingual language model such as XLM-R (Conneau et al, 2020) or mBERT (Devlin et al, 2019) to capture the syntactic and semantic characteristics. Following Conia et al (2021), we obtain word representations e ∈ R |S|×d by concatenating the hidden states of the four top-most layers of the language model, where |S| is the sequence length and d is the dimension of the hidden state.…”
Section: Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we present a simple basic SRL model and enhance the model with the contextualized word representations from BERT for further improvements. Besides, we also present a MTL framework to improve the SRL performance by learning from multiple heterogeneous datasets simultaneously (Conia et al, 2021).…”
Section: Approachmentioning
confidence: 99%
“…However, since idiomaticity is a frequent phenomenon that can be observed in all languages, idiomatic expressions should play an important role in NLP. Indeed, their identification and understanding is crucial not only for Natural Language Understanding tasks such as Word Sense Disambiguation (Bevilacqua et al, 2021b), Semantic Role Labeling (Conia et al, 2021) and Semantic Parsing (Bevilacqua et al, 2021a), but also for Machine Translation (Edunov et al, 2018;Liu et al, 2020), Question Answering (Mishra and Jain, 2016) and Text Summarization (Chu and Wang, 2018), inter alia.…”
Section: Introductionmentioning
confidence: 99%